Safeguarding Workers: A Study of Health and Safety Representatives in the Queensland Coalmining Industry, 1990-2013 - Walters, David; Johnstone, Richard; Quinlan, Michael; Wadsworth, Emma (Relations industrielles / Industrial Relations, 2016)
This paper explores the practice of worker representation coalmining in Australia, in which there are both serious risks to health and safety and where regulatory provisions on worker representation on health and safety are longstanding. Despite their longevity, their operation has been little studied. The aim of the paper is to address this gap by examining the quality of the practice of worker representation in the sector. In particular, it explores strategies used by representatives to undertake their role in the context of the hostile industrial relations that are characteristic of coalmining. It examines documentary records of statutory inspections by worker representatives and government mines inspectors and analyses the content of qualitative interviews. It finds that the representatives address serious and potentially fatal risks in their activities and make effective use of their statutory powers in doing so, including their power to suspend operations they deem to be unacceptably dangerous. Nevertheless, they strive to operate within the boundaries of regulation in order to offset the negative influences of a hostile labour relations climate, As well as cautious use of their powers to order the cessation of operations where they deem the risks to be unacceptable, they also avoid accusations of unnecessarily impeding production and engaging with labour relations matters that are outside their statutory remit, through good communication between themselves and other workplace representatives. This is made possible by support from the relatively high level of workplace trade union organization present in the mines and further support derived from the trade union more widely and from the unique two-tier form of representation provided for by legislation. Both ensure the representatives are well informed, well trained and supported in their role. Overall, the study highlights the positive role representatives and unions play in preventive health and safety even in hostile labour relations climates.